Attitudes towards elderly care among older and younger Finns - Tanskanen Antti; Kallio Johanna; Danielsbacka Mirkka (Turku Center for Welfare Research, 2025)
In this study, we investigated public opinions towards elderly care using nationally representative data collected in Finland in 2012. Respondents represent an older generation (born between 1945 and 1950, n = 1,959) and their adult children (born between 1962 and 1993, n = 1,652). We analysed respondents’ opinions towards financial support, practical help and care for elderly people. We found that older adults were more likely than younger adults to report that financial support towards elderly people should come from the state rather than family. However, similar differences between generations were not found in reports relating to practical help and care. Similar results were found when only parent-child dyads (n = 779) were included. We also found that several socioeconomic and family-related variables were associated with public opinions of elderly care in both generations. The results are discussed in the context of self-interest perspective.